The Basel III framework for liquidity standards and monetary policy implementation - Ulrich Bindseil; Jeroen Lamoot (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
Basel III introduces for the first time an international framework for liquidity risk regulation, reflecting the experience of excessive liquidity risk taking of banks in the run up to the financial crisis that erupted in August 2007, and associated negative externalities. As central banks play a crucial role in the liquidity provision to banks during normal times and in a financial crisis, the treatment of central bank operations in the regulation is obviously important. To ensure internalisation of liquidity risks (i.e. pricing of liquidity risk) and to address excessive reliance ex ante on central bank liquidity support by the banks, the regulation deliberately does not establish a direct close link with the monetary policy operational framework. While this reflects the purpose of the regulation and is also natural outcome of an international rule being applied under a multitude of very different monetary policy operational frameworks, this paper shows that the interaction between the two areas can be substantial, depending on the operational and collateral framework of the central bank. This implies the need for further study and the development of policies at the central bank and regulatory/supervisory side on how to handle these potential interactions in practice.
Keywords: E58; G21; G28; 330; Basle III; liquidity risk; banking regulation; monetary policy implementation; Basel II; Bankenliquidität; Risiko; Geldpolitik; Welt